Adverse Effects Cause Varenicline Discontinuation: A Meta-Analysis - D. Drovandi, Aaron; C. Chen, Carla; D. Glass, Beverley (Current Drug Safety, 2016)
Purpose: Varenicline, the newest agent marketed for smoking cessation is regarded as effective in providing prolonged smoking abstinence. However, its adverse effect profile may cause discontinuation, potentially reducing smoking abstinence rates, thus requiring an examination of the frequency and impact of adverse effects on discontinuation. Methods: We sought only Randomised Controlled Trials (RCTs) evaluating the effectiveness and safety of varenicline on humans, with a follow-up period of at least three months and an average Fagerstrom Test for Nicotine Dependence (FTND) score at least 5 (moderate dependence) for both the active and placebo groups. PubMed, Medscape, JCU One Search, ClinicalTrials.gov (U.S.), and the Cochrane Collaboration from January 2006 to January 2015 were searched. Fixed and random effects models were run to determine relationships between adverse effects and premature discontinuation from varenicline. Results: 12 RCTs were included, involving 5 459 patients, with those receiving varenicline found to be nearly twice as likely (Odds ratio (OR) = 1.82 [1.47; 2.26]) to experience adverse effects compared to those patients on a placebo. The active group experienced nearly a 1.5 times higher (OR = 1.47 [1.19; 1.81]) rate of discontinuation. Nausea, insomnia, and headache are the most commonly reported adverse effects, with ORs of 4.40 [3.80; 5.11], 1.75 [1.48; 2.08], and 1.20 [1.02; 1.41] respectively. Conclusion: Adverse effects experienced during varenicline treatment appear to be associated with higher discontinuation, which are linked to lowered smoking cessation rates, suggesting a need for strategies to minimise the impacts of adverse effects, to better ensure adherence.
Keywords: Adherence